Problematika Pembelajaran Pada Masa Pandemik Guru Sekolah Dasar Negeri 173167 Kecamatan Sipahutar Kabupaten Tapanuli Utara - Rosbita Simanjuntak (Institut Agama Kristen Negeri Tarutung, 2020)
AbstractThis study aims to determine the constraints at pandemic 19 in Tapanuli Utara . This type of research was descriptive qualitative. Data collection techniques are done by interviewing and filling out questionnaires online. Analysis of the data used in this study are data collection, data reduction, data presentation and conclusions. The results showed that the constraints experienced by teachers during pandemic 19 were learning applications, internet networks and devices, learning management, assessment, perception’s parent, develop interest student, and supervision.